SEKURITISASI TERHADAP PARA PENGUNGSI DAN PENCARI SUAKA DI AUSTRALIA TAHUN 2021 - 2023 - Catherine Andrea Marselamitha; Muharjono (Jurusan Ilmu Hubungan Internasional, 2025)
This research discusses Australia's securitization process towards refugees and asylum seekers in 2021-2023 with the aim of understanding Australia's views and decisions in securitizing issues related to refugees and asylum seekers. Through this research, the discussion will be examined using securitization theory to analyze how Australia's implementation of policies towards refugees and asylum seekers is a form of securitization. The securitization began with the speech act given by Scott Morrison and Anthony Albanese in 2021-2023 to make the arrival of refugees and asylum seekers in Australia as a security issue, both the security of refugees and asylum seekers themselves from the threat of drowning at sea and the security of Australia from concerns about transnational crime due to the arrival of refugees and asylum seekers through illegal routes from the sea. As a form of emergency measures from the given speech act, related policies such as detention policies in detention facilities and border protection policies through patrols in Australian sea areas were then implemented. Keywords : Securitization, Australia, Refugees, Asylum Seekers